Identifying the Effective Factors and Presenting the Practical Model of Knowledge Management in the Improvement of Employees with the Approach of Examining the Role of Technical Knowledge of Retired Employees of the National Company of Southern Oil-Bearing Regions - Fatemeh Rezaei; Fatemeh Larki; Soraya Badri (توسعه اجتماعی)
The purpose of this study was to analyze the application of knowledge management for staff improvement with emphasis on the pathology of technical knowledge of retired employees. A qualitative research with applied purpose was performed by sequential analytical mixed method. The statistical population of this study was two groups. The first group was 30 persons of faculty members of petroleum engineering at Khuzestan Islamic Azad University and the secend one was 100 persons of managers at National Ianian South Oil Company. The statistical sample of the managers was selected by snowball method and the faculty members were selected by targeted selective sampling from 20 persone of each groups. Sample size was selected based on Delphi technique. Data were collected using a researcher-made questionnaire. Its face and content validity was verified using expert opinion and pilot study results. Research questions were adjusted based on the main components and factors of knowledge management theory infrastructure, comparison of National Ianian South Oil Company subsidiaries with several brand oil companies, how to return staff technical knowledge, evaluation of researcher-made knowledge management model. With use of Delphi technique elite opinion was examined in 3 separate stages. By using content analysis method and descriptive statistics, the research data were classified, numerically coded based on the order of participation in interviews, surveyed, scored and analyzed. The results show that the retirement cycle of technical knowledge of retired employees was weak and this floating gold goes out with retired staff from the system, while using retired staff in thought and consulting rooms, working as a technical lecturer, part-time collaboration can be used when needed. Finally, an applied model of knowledge management, derived from this research, is presented.